2017
DOI: 10.4236/ce.2017.812130
|View full text |Cite
|
Sign up to set email alerts
|

Between Natural Language and Mathematical Symbols (<, >, =): The Comprehension of Pre-Service and Preschool Teachers- Perspective of Numbers

Abstract: This article presents a quantitative and qualitative study comparing how pre-service and preschool teachers perceive the relational symbols (<, > and =), perspective of numbers. The study population comprised 71 pre-service teachers participating in a course dedicated to teaching and learning early childhood mathematics and 149 in-service preschool teachers. A large proportion of the participants did not answer the questions correctly or give suitable reasons for their answers. There was a significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…This study, similar to a previous study by Hassidov and Ilany (2017) found that most of the participants failed to answer the questions correctly. The justifications given to the four questions show a significant difference between the pre-service and preschool teachers with respect to how many justified their an-…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This study, similar to a previous study by Hassidov and Ilany (2017) found that most of the participants failed to answer the questions correctly. The justifications given to the four questions show a significant difference between the pre-service and preschool teachers with respect to how many justified their an-…”
Section: Discussionsupporting
confidence: 91%
“…even when the answer given was correct ("X"), the justification was generally incorrect. These findings support the study regarding how pre-service teachers and preschool teachers understand relational symbols (<, >, =) with respect to numbers (Hassidov & Ilany, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations